2023
DOI: 10.1063/5.0140641
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of discretization strategies for the model-free information-theoretic assessment of short-term physiological interactions

Abstract: This work presents a comparison between different approaches for the model-free estimation of information-theoretic measures of the dynamic coupling between short realizations of random processes. The measures considered are the mutual information rate (MIR) between two random processes [Formula: see text] and [Formula: see text] and the terms of its decomposition evidencing either the individual entropy rates of [Formula: see text] and [Formula: see text] and their joint entropy rate, or the transfer entropie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…The analysis of the coupling of the bivariate system S = { RR , RESP } using MIR highlights that the coupling between RR and RESP is not lost during different paced breathing rates ( Mary et al, 2018 ), being the slight decrease observed in Figure 9 from the SB to the C10 phase not significant, and is followed by a complete recovery in C15 and C20. Such results are similar to what was reported in ( Barà et al, 2023 ). A decrease in nonlinearities was observed in the C10 phase when compared with the other experimental conditions.…”
Section: Analysis Of Cardiorespiratory Interactionssupporting
confidence: 93%
See 3 more Smart Citations
“…The analysis of the coupling of the bivariate system S = { RR , RESP } using MIR highlights that the coupling between RR and RESP is not lost during different paced breathing rates ( Mary et al, 2018 ), being the slight decrease observed in Figure 9 from the SB to the C10 phase not significant, and is followed by a complete recovery in C15 and C20. Such results are similar to what was reported in ( Barà et al, 2023 ). A decrease in nonlinearities was observed in the C10 phase when compared with the other experimental conditions.…”
Section: Analysis Of Cardiorespiratory Interactionssupporting
confidence: 93%
“…The MIR of the bivariate process S = { X , Y } is defined as the limit, if it exists, of the rate at which the MI between dynamic sequences taken from X and Y increases over time ( Komaee, 2020 ; Miao et al, 2020 ) The MIR serves as a dynamic measure for the information shared per unit of time between two dynamical systems and was adopted in various forms to quantify dynamic interactions among physiological processes ( Baptista and Kurths, 2008 ; Mijatovic et al, 2021 ; Faes et al, 2022 ). This measure of dynamic coupling can be decomposed in terms of other information-theoretic measures, offering valuable insights into the dynamics of each process and the coupling relationships within the bivariate system ( Barà et al, 2023 ). A possible decomposition of MIR is where H X and H Y denote the entropy rate of X and Y , respectively, and H X , Y their joint entropy rate.…”
Section: Framework For the Surrogate Data Analysis Of Dynamic Correla...mentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of new tools for the quantification of high order interactions is opening new possibilities in the field of network physiology, which aims to address the fundamental question of how physiological networks collectively behave to maintain human body in healthy conditions (Bashan et al, 2012;Lin et al, 2020;Ivanov 2021). Historically, the study of physiological time series has seen a shift from the univariate analysis of individual time series, where measures such as the approximate entropy (Pincus, 1991), the sample entropy (Richman and Moorman, 2000) and the corrected conditional entropy (Porta et al, 1998) have been introduced to characterize the predictable dynamics of a physiological system, to the bivariate analysis of two time series, where symmetric or causal measures based on cross-entropies (Porta et al, 1999;Faes et al, 2011), mutual information (Valderas, 2019) and its rate (Barà et al, 2023), directed information (Massey, 1990) or transfer entropy (Schreiber, 2000;Faes et al, 2014) have been used extensively to quantify the information shared and transferred between pairs of physiological systems. Multivariate analyses involving more than two physiological time series have been then introduced to quantify how the information transferred between processes is affected by the rest of the network.…”
Section: Introductionmentioning
confidence: 99%